EVALUASI KURIKULUM TVET BERBASIS INDUSTRI: PENGUATAN LINK AND MATCH MELALUI INOVASI TEKNOLOGI DAN KETERLIBATAN STRATEGIS INDUSTRI - Fajar Maulana; Meiyaldi Eka Putra; Jimmi Zamora; Muhammad Anwar; Wakhinuddin (Smart Education, 2026)
Abstract: This study aims to evaluate the effectiveness of an industry based Technical Vocational Education and Training (TVET) curriculum through the enhancement of link-and-match programs, technological innovation, and strategic industry engagement. A Systematic Literature Review (SLR) approach was employed following the PRISMA 2020 guidelines. Data were collected from reputable databases, including Scopus, Web of Science (WoS), Google Scholar, and Crossref, covering publications from the last ten years. An initial search identified approximately 500 articles, which were subsequently screened through the stages of identification, screening, eligibility, and inclusion, resulting in 20 high-quality and relevant studies. The selected articles served as the foundation for developing a conceptual evaluation model and operationalizing the research variables. Furthermore, Structural Equation Modeling–Partial Least Squares (SEM-PLS) was utilized to examine the relationships among strategic industry engagement, technological innovation, link-and-match programs, and TVET curriculum effectiveness. The findings reveal that strategic industry engagement contributes 42.1%, technological innovation 35.6%, and link-and-match programs 39.4% to curriculum effectiveness, with a coefficient of determination (R²) of 74.2%, indicating strong explanatory power. These results highlight that sustained industry collaboration, adaptive technological integration, and systematic implementation of link-and-match initiatives are critical factors in enhancing curriculum relevance and graduate employability. This study provides both theoretical and practical insights for developing responsive, sustainable, and industry-aligned TVET curricula capable of addressing the evolving demands of the modern workforce. Keywords: TVET Curriculum Evaluation, Industry Engagement, Technological Innovation Link and Match Program, Curriculum Effectiveness. Abstrak: Penelitian ini bertujuan mengevaluasi efektivitas kurikulum Technical Vocational Education and Training (TVET) berbasis industri melalui penguatan program link and match, inovasi teknologi, dan keterlibatan strategis industri. Penelitian menggunakan pendekatan Systematic Literature Review (SLR) berdasarkan pedoman PRISMA 2020. Data diperoleh dari basis data Scopus, Web of Science (WoS), Google Scholar, dan Crossref dengan rentang publikasi sepuluh tahun terakhir. Dari sekitar 500 artikel yang teridentifikasi, proses seleksi melalui tahapan identifikasi, penyaringan, kelayakan, dan inklusi menghasilkan 20 artikel utama yang relevan dan berkualitas. Temuan kajian literatur digunakan untuk membangun model konseptual evaluasi kurikulum TVET berbasis industri serta operasionalisasi variabel penelitian. Analisis dilakukan menggunakan Structural Equation Modeling–Partial Least Squares (SEM-PLS) untuk menguji pengaruh keterlibatan strategis industri, inovasi teknologi, dan program link and match terhadap efektivitas kurikulum TVET. Hasil penelitian menunjukkan bahwa keterlibatan strategis industri memberikan kontribusi sebesar 42,1%, inovasi teknologi sebesar 35,6%, dan program link and match sebesar 39,4%, dengan nilai koefisien determinasi (R²) sebesar 74,2%. Temuan ini menegaskan bahwa kolaborasi industri yang berkelanjutan, integrasi teknologi yang adaptif, dan implementasi link and match yang sistematis merupakan faktor utama dalam meningkatkan relevansi kurikulum serta kesiapan lulusan menghadapi kebutuhan industri modern. Kata kunci: Evaluasi Kurikulum TVET Berbasis Industri, Penguatan Link and Match Inovasi Teknologi, Keterlibatan Strategi Industri.